Pengaruh Employee Engagement Dan Loyalitas Terhadap Kinerja Karyawan Generasi Z Di Daerah Khusus Jakarta - Muhammad Nadhif Nabhan; Adi Nugroho (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF EMPLOYEE ENGAGEMENT AND LOYALTY ON THE PERFORMANCE OF GENERATION Z EMPLOYEES IN THE SPECIAL AREA OF JAKARTA Abstract. This study aims to analyze the influence of employe engagement and loyalty on the performance of Generation Z employes in the Special Region of Jakarta. The presence of Generation Z in the workforce brings its own challenges for organizations, one of which is the high phenomenon of job hopping that indicates low loyalty and can disrupt the sustainability of the organization. This research uses an associative quantitative method. Primary data collection was conducted thru the distribution of questionnaires to 102 respondents. The sample selection used the purposive sampling method with criteria for individuals born between 1995-2012, working in the Special Region of Jakarta, and having a minimum work period of six months. The data analysis used includes classical assumption tests, multiple linear regression analysis, coefficient of determination tests, and hypothesis tests (t-test and F-test) using SPSS version 27 software. The research results show several key findings. Partially, employe engagement has a positive and significant effect on the performance of Generation Z employes in the Special Region of Jakarta. Partially, loyalty has a positive and significant effect on the performance of Generation Z employes in the Special Region of Jakarta. Simultaneously, employe engagement and loyalty together have a significant effect on the performance of Generation Z employes. Based on the adjusted R-squared coefficient test, the variables of employe engagement and loyalty can explain 51.3% of the variation in employe performance, while the remaining 48.7% is explained by other factors outside this research model.The conclusion of this study shows that improving work engagement and loyalty of Generation Z employes is very important for the company to encourage the creation of work results oriented toward achieving organizational goals.